Modification of Ti-Zr-Ni alloys by powerful plasma stream of different gases - Bazdyrieva, S.V.; Garkusha, I.E.; Makhlaj, V.A.; Malykhin, S.V.; Petrov, Yu.V.; Pugachоv, A.T. (Вопросы атомной науки и техники, 2015)
The effects of irradiation by hydrogen, helium and argon plasma heat loads of 0.4 … 0.6 MJ/m2 on the change of morphology, structure and phase composition of Ti41.5Zr41.5Ni17 alloy are investigated. The initial state of such alloy is characterized by presence of a crystal- approximant 1/1 phase (W-phase) with lattice constant аW = 1.428 ±0.0003 nm, Laves phase (L phase) with the lattice period a = 0.6043 ± 0.0003 nm and an icosahedral quasi-crystalline phase (i-phase) with quasi-crystalline parameter aq= 0.5175 ±0.0003 nm. Plasma irradiation causes formation of the icosahedral quasi-crystalline phase in re-solidified layer with depth up to 100 μm. The substructure parameters: size of the coherence area, the value of micro-strain, phason defect concentration and the value of residual macro-stresses are determined by the plasma parameters.